Building public-private partnerships for agricultural innovation - Hartwich, Frank; Tola, Jaime; Engler, Alejandra; González, Carolina; Ghezan, Graciela; Vázquez-Alvarado, Jorge M. P.; Silva, José Antonio; Espinoza, José de Jesús; Gottret, M.V. (International Food Policy Research Institute, 2007)
Public-private partnerships are a new way of carrying out research and development (R&D) in Latin America's agricultural sector. These partnerships spur innovation for agricultural development and have various advantages over other institutional arrangements fostering R&D. This report summarizes the experiences of a research project that analyzed 125 public-private research partnerships (PPPs) in 12 Latin American countries. The analysis indicates that several types of partnerships have emerged in response to the various needs of the different partners. Nevertheless, public-private partnerships are not always the most appropriate mechanism by which to carry out R&D and foster innovation in agriculture. Sometimes, it is more efficient to organize research via participatory projects or through research contracts.